2017 IEEE International Conference on Robotics and Automation (ICRA) 2017
DOI: 10.1109/icra.2017.7989199
|View full text |Cite
|
Sign up to set email alerts
|

Modeling cooperative navigation in dense human crowds

Abstract: For robots to be a part of our daily life, they need to be able to navigate among crowds not only safely but also in a socially compliant fashion. This is a challenging problem because humans tend to navigate by implicitly cooperating with one another to avoid collisions, while heading toward their respective destinations. Previous approaches have used handcrafted functions based on proximity to model human-human and human-robot interactions. However, these approaches can only model simple interactions and fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 29 publications
1
77
0
1
Order By: Relevance
“…The potential term captures interactions based on the relative distances of humans in the crowd and results in a probabilistic model that has been shown to capture joint collision avoidance behavior. This has been extended in [31] by replacing the handcrafted potential term with a locally trained interaction model based on occupancy grids. However, these approaches model interactions based on relative distances and orientations, ignoring other features such as velocity and acceleration.…”
Section: A Modeling Human Interactions For Navigationmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential term captures interactions based on the relative distances of humans in the crowd and results in a probabilistic model that has been shown to capture joint collision avoidance behavior. This has been extended in [31] by replacing the handcrafted potential term with a locally trained interaction model based on occupancy grids. However, these approaches model interactions based on relative distances and orientations, ignoring other features such as velocity and acceleration.…”
Section: A Modeling Human Interactions For Navigationmentioning
confidence: 99%
“…More recent approaches such as [1], [28], [31] model the joint distribution of future trajectories of all interacting agents through a spatially local interaction model. Such a joint distribution model is capable of capturing the dependencies between trajectories of interacting humans, and results in socially compliant predictions.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of artificial intelligence technologies, mobile robot navigation has many vital applications in crowded pedestrian environments such as hospitals, shopping malls, and canteens. In these scenarios with dense crowds, navigating robots safely and efficiently is a crucial, yet still challenging, problem [1].…”
Section: Introductionmentioning
confidence: 99%
“…The main factors influencing pedestrian motion are interactions among pedestrians, the environment, and the location of their destination. By taking into account the interaction between pedestrians, the accuracy of the motion models can be significantly increased [1]- [5]. It was shown that using interaction-aware motion models for dynamic agent This work has received funding from the European Union Seventh Framework Programme FP7, project EUROPA2, Grant No.…”
Section: Introductionmentioning
confidence: 99%
“…(ii) The approaches are not scalable to dense crowds since they use pairwise interactions between all agents [1]- [3], which leads to a quadratic complexity in number of agents, and therefore real-time computation is only feasible for a small number of agents. (iii) Static obstacles are neglected [1], [4], [5] and (iv) knowledge about a set of potential destinations is assumed [1], [3], [5].…”
Section: Introductionmentioning
confidence: 99%